Tannic acid TA (at) beta nucleating agent doped gel electrolyte, preparation method and application

The synthesis of tanninic acid @β nucleating agent doped with gel electrolytes through gamma rays or electron beams has solved the problems of poor flammability and thermal stability of electrolytes in traditional lithium-ion batteries, and achieved the improvement of energy density and cycle stability of lithium-ion batteries.

CN119674206AActive Publication Date: 2025-03-21RES INST OF CHEM DEFENSE PLA ACAD OF MILITARY SCI
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411722367.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-21
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

Traditional lithium-ion batteries have problems such as poor flammability, volatility and thermal stability of electrolytes, which leads to limited improvement in battery performance and difficulty in expanding their application range.

Method used

The titonic acid @β nucleating agent is synthesized by γ ray or electron beam method to dopant new gel electrolytes, and an electrolyte that isolates electron transporting lithium ions in the lithium battery through in situ polymerization.

Benefits of technology

It improves the energy density and cycle stability of lithium-ion batteries, slows down the risk of thermal runaway in batteries under high energy density, and expands the application range of batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674206A_ABST
    Figure CN119674206A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of energy storage materials, and particularly discloses a tannic acid TA-beta nucleating agent doped gel electrolyte, a preparation method and application. According to the gel electrolyte prepared through the radiation in-situ polymerization technology, the problem that the preparation technology of the gel electrolyte is complex is effectively solved. The lithium ion battery using the gel electrolyte is remarkably improved in energy density and cycle life, and stable electrochemical performance can be maintained. Due to the high free radical capture consumption characteristic, the capacity retention capacity of the battery under the conditions of high voltage and high rate is improved, and the discharge specific capacity of the obtained gel electrolyte battery under the condition of 5C is about 169mAh / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energy storage materials, and specifically discloses a tannic acid TA@β nucleating agent doped gel electrolyte, a preparation method thereof, and an application thereof. Technical Background

[0002] With the continuous growth of energy demand in modern society and the pursuit of environmentally friendly energy solutions, lithium-ion batteries have become the preferred energy source for portable electronic devices, electric vehicles, and large-scale energy storage systems due to their advantages such as high energy density, long cycle life, and low self-discharge rate. However, traditional lithium-ion batteries have some limitations, such as the flammability, volatility, and poor thermal stability of the electrolyte, which limit the further improvement of battery performance and the expansion of the application scope.

[0003] Gel electrolytes combine the high safety of solid electrolytes and the high ionic conductivity of liquid electrolytes, and are expected to become the key materials for the next generation of lithium-ion batteries. Although many literatures (Ma, Chao, et al. InfoMat. 2022, 002, 004; Nan Chen, et al. Adv, Energy Mater, 2018, 8, 12; Shuai Tang, Wei Guo, et al. Adv, EnergyMater, 2020, 11, 2) and patents (Chinese invention patent CN118344353A; Chinese invention patent CN118146447A) report that gel electrolytes show great potential in terms of safety and electrochemical performance, they still face some challenges in practical applications. For example, the preparation process of gel electrolytes is complex, and under harsh conditions such as high rate, high voltage, and high temperature in the battery, there are many side reactions between the internal electrolyte and the electrode, resulting in a sharp decline in the cycle stability of the battery and other problems.

[0004] Therefore, it is necessary to seek a gel electrolyte with excellent performance to overcome the above technical problems. Summary of the Invention

[0005] The purpose of the present invention is to develop a method using gamma rays or electron beams to synthesize a novel gel electrolyte (TA@β-x / GPE-y) composite material doped with tannic acid @β nucleating agent (TA@β-x represents the mass of tannic acid @β nucleating agent, GPE-y represents the gel fraction, where 0 < x < 20, 0 < y < 60%), and in-situ polymerize the composite material inside a lithium battery as an electrolyte for isolating electron transmission and lithium ions.

[0006] The technical solution adopted by the present invention is as follows:

[0007] In the first aspect, the present invention provides a preparation method of a TA@β nucleating agent doped gel electrolyte, including the following steps:

[0008] S1: Weigh tannic acid TA and β nucleating agent according to a mass ratio of 1:5 to 5:1, then mix them into water, stir at room temperature to react fully, separate, purify and dry to obtain TA@β free radical scavenger;

[0009] S2: adding the free radical scavenger obtained in step S1, the phosphate monomer, and the acrylate monomer to the lithium salt electrolyte, and stirring and mixing; the addition amounts are 1 to 100 parts by mass of the free radical scavenger, and 200 to 600 parts by mass of the phosphate monomer and the acrylate monomer;

[0010] Wherein, the lithium salt is one or a mixture of two or more selected from lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium tetrafluoroborate, lithium bis(difluorosulfonyl imide) and lithium bis(trifluoromethylsulfonyl imide); the phosphate monomer is one or a mixture of two or more selected from di[2-(methacryloyloxy)ethyl]phosphate, di[2-(acryloyloxy)ethyl]phosphate, vinyl dimethyl phosphate, vinyl diethyl phosphate, vinyl dipropyl phosphate, 2-(methacryloyloxy)ethyl-2-(trimethylamino)ethyl phosphate; the acrylate monomer is one or a mixture of two or more selected from trimethylolpropane triacrylate, cyanuric acid triacrylate, pentaerythritol tetraacrylate, 1,6-hexanediol diacrylate;

[0011] S3: irradiating the mixed solution obtained in step S2 with γ rays or electron beams; after the irradiation, a new type of gel electrolyte is obtained.

[0012] Preferably, in step S1, the stirring reaction time at room temperature is 1-10 days.

[0013] Preferably, in step S1, the concentration of tannic acid is 5 to 50 g / L.

[0014] Preferably, in step S2, the mass concentration of the free radical scavenger is 0.1-10 g / L, and the mass concentrations of the phosphate monomer and the acrylate monomer are 20-60 g / L and 20-60 g / L, respectively.

[0015] Furthermore, in step S2, the stirring time is 0.1-48h.

[0016] Preferably, in step S3, the irradiation absorbed dose rate is 10-150 Gy / min, and the absorbed dose is 0.1-20 kGy.

[0017] Preferably, in step S3, the radiation source generating the gamma rays is 60 Co source or 137 Cs source; the electron beam is generated by an electron accelerator with an energy of 0.1 to 10 MeV.

[0018] In a second aspect, the present invention provides a TA@β-doped gel electrolyte as described in the first aspect.

[0019] In a third aspect, the present invention provides an application of the TA@β-doped gel electrolyte lithium-ion battery described in the second aspect.

[0020] TA@β free radical scavenger, phosphate monomers and acrylate monomers are added to the lithium salt electrolyte, stirred and mixed, and then injected into the lithium ion battery, and then a new type of gel-type lithium battery is synthesized by in-situ polymerization of gamma rays or electron beams.

[0021] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery uses the TA@β-doped gel electrolyte described in the first aspect as an electrolyte.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1) Currently, lithium-ion batteries pursue higher energy density. By adding copolymers with high-voltage resistance to the electrolyte, the gel skeleton formed can adapt to a higher voltage range, effectively improving the energy density of gel-type batteries. At the same time, flame-retardant phosphate compounds can slow down / inhibit the occurrence of thermal runaway of batteries at high energy density, significantly improving the long-term application of lithium-ion batteries.

[0024] 2) Under high energy density conditions, efficient charge and discharge capabilities can significantly expand the application range of batteries. Adding specially designed free radical capture additives to gel electrolytes can significantly slow down / inhibit battery side reactions under high energy density conditions, allowing the battery to have excellent capacity retention under higher rate conditions and meet efficient charge and discharge capabilities.

[0025] 3) Use gamma rays or electron beams to synthesize gel electrolytes. This method has an activation energy close to zero, so the reaction conditions are relatively mild and can be completed at room temperature. In addition, this process does not require the addition of any additional initiators, thus ensuring the high purity of the product. At the same time, the monomer reaction rate and degree can be changed by adjusting the distance between the sample and the radiation source and the irradiation time, forming a gel-type battery in situ. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Infrared spectrum of tannic acid composite β-nucleating agent.

[0027] The horizontal axis is the wave number, in cm -1 , the ordinate is the transmittance, the unit is %, I, II and III represent TA, β nucleating agent and TA@β, respectively.

[0028] Figure 2UV absorption spectra of DPPH· solutions after reaction with TA and TA@β.

[0029] The horizontal axis is wavelength in nm, and the vertical axis is absorbance.

[0030] Figure 3 C NMR spectrum of the radiation synthesized gel electrolyte. The abscissa is the chemical shift in ppm, and the ordinate is the intensity.

[0031] Figure 4 Voltage-capacity curve of TA@β-doped new gel electrolyte battery at 3-4.8V, 5C conditions.

[0032] The horizontal axis is the specific capacity, the unit is mAh / g, and the vertical axis is the voltage, the unit is V. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0035] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0036] Example 1

[0037] A novel TA@β-doped gel electrolyte composite material for high specific energy lithium battery, the preparation method of which is as follows:

[0038] 1) In a container containing 100 mL of deionized water, 1 g of tannic acid TA and 1 g of β nucleating agent were added respectively, ultrasonically mixed and stirred for 1 day. After the reaction was completed, the white particles in the container were filtered, ultrasonically washed alternately with distilled water and ethanol for multiple times, and dried in a vacuum oven at 60° C. for later use. The obtained particles were named TA@β free radical scavenger.

[0039] 2) In a reaction vessel containing 10 mL of 1 mol LiPF6 electrolyte solvent, 0.2 g of vinyl diethyl phosphate monomer, 0.3 g of pentaerythritol tetraacrylate monomer and 20 mg of the TA@β free radical scavenger obtained in step 1) were stirred for 30 minutes to mix evenly. After mixing, the mixture was sent to a cobalt source chamber for γ irradiation at a dose rate of 40 Gy / min and an absorbed dose of 2 kGy. The obtained product was named TA@β-x / GPE-y, wherein x=20, y=30% (x represents the mass of the TA@β free radical scavenger and y represents the gel fraction of the gel electrolyte).

[0040] The tannic acid TA composite β nucleating agent material prepared by the present invention was characterized by infrared spectroscopy. Figure 1 As shown in the figure, I is the infrared spectrum of tannic acid TA, II is the infrared spectrum of β nucleating agent, and III is the infrared spectrum of TA@β. It can be clearly seen that at 1650cm -1 The carbon-carbon double bond peak of tannic acid TA appeared in the infrared spectrum of TA@β, proving the successful preparation of the composite material. The C NMR spectrum of the composite gel was further characterized, as shown in Figure 2. Figure 2 The C peaks shown are completely consistent with the gel structure, proving the successful preparation of the composite gel material. At the same time, to verify whether TA@β has the ability to capture free radicals, the UV absorption spectrum of the DPPH solution after the reaction of tannic acid TA and TA@β was tested, as shown in Figure 2. Figure 3 As shown, the DPPH solution has an obvious peak at a wave number of 522nm. When tannic acid TA is added, the peak of the same DPPH solution disappears. Similarly, the peak of the DPPH solution with TA@β also disappears, which fully proves that the composite material has excellent free radical capture ability.

[0041] Study on the performance of TA@β-doped new gel electrolyte in lithium-ion batteries

[0042] The electrolyte obtained in Example 1 containing 20 mg TA@β free radical scavenger, 0.2 g vinyl diethyl phosphate monomer and 0.3 g pentaerythritol tetraacrylate monomer was injected into a lithium battery with lithium nickel cobalt manganese oxide as the positive electrode, a lithium sheet as the negative electrode and Celgard2035 as the separator, and then the packaged battery was irradiated with gamma rays or electron beams, and finally the electrochemical properties of the irradiated gel-type battery were tested using the Wuhan Blue Electric charge / discharge system.

[0043] The TA@β-doped new gel electrolyte battery was tested at 3-4.8V, 5C conditions. Figure 4 The horizontal axis is the specific capacity, the unit is mAh / g, and the vertical axis is the voltage, the unit is V. It can be clearly seen that under high voltage and high rate conditions, the gel-type battery containing the free radical scavenger has excellent charge and discharge capabilities.

[0044] Example 2

[0045] In step 2) of Example 1 60 The Coγ-ray was replaced by an electron beam generated by an electron accelerator, the absorbed dose rate was 40 kGy / min, the absorbed dose was 2 kGy, and the other conditions were the same as in Example 1, to obtain a TA@β-x / GPE-y gel composite material for lithium batteries, wherein x=20 and y=30%.

[0046] Example 3

[0047] The absorbed dose rate in step 2) of Example 1 was changed to 60 Gy / min, and the other conditions were the same as those of Example 1, to obtain a TA@β-x / GPE-y gel composite material for lithium batteries, wherein x=20 and y=29%.

[0048] Example 4

[0049] The absorbed dose rate in step 2) of Example 1 was changed to 80 Gy / min, and the other conditions were the same as those of Example 1, to obtain a TA@β-x / GPE-y gel composite material for lithium batteries, wherein x=20 and y=27%.

[0050] Example 5

[0051] The absorbed dose rate in step 2) of Example 1 was changed to 100 Gy / min, and the other conditions were the same as those of Example 1, to obtain a TA@β-x / GPE-y gel composite material for lithium batteries, wherein x=20 and y=25%.

[0052] Example 6

[0053] The absorbed dose rate in step 2) of Example 1 was changed to 120 Gy / min, and the other conditions were the same as those of Example 1, to obtain a TA@β-x / GPE-y gel composite material for lithium batteries, wherein x=20 and y=21%.

[0054] Example 7

[0055] The absorbed dose in step 2) of Example 1 was changed to 4 kGy, and the other conditions were the same as those of Example 1, to obtain a TA@β-x / GPE-y gel composite material for lithium battery, wherein x=20 and y=33%.

[0056] Example 8

[0057] The absorbed dose in step 2) of Example 1 was changed to 6 kGy, and the other conditions were the same as Example 1, to obtain a TA@β-x / GPE-y gel composite material for lithium battery, wherein x=20 and y=38%.

[0058] Example 9

[0059] The absorbed dose in step 2) of Example 1 was changed to 8 kGy, and the other conditions were the same as Example 1, to obtain a TA@β-x / GPE-y gel composite material for lithium battery, wherein x=20 and y=47%.

[0060] Example 10

[0061] The absorbed dose in step 2) of Example 1 was changed to 10 kGy, and the other conditions were the same as Example 1, to obtain a TA@β-x / GPE-y gel composite material for lithium battery, wherein x=20 and y=60%.

[0062] Embodiment 11

[0063] The free radical scavenger in step 2) of Example 1 was changed to 1 mg, and the other conditions were the same as Example 1 to obtain a TA@β-x / GPE-y gel composite material for lithium batteries, wherein x=1 and y=30%.

[0064] Example 12

[0065] The free radical scavenger in step 2) of Example 1 was changed to 5 mg, and the other conditions were the same as Example 1 to obtain a TA@β-x / GPE-y gel composite material for lithium batteries, wherein x=5 and y=30%.

[0066] Embodiment 13

[0067] The free radical scavenger in step 2) of Example 1 was changed to 10 mg, and the other conditions were the same as Example 1 to obtain a TA@β-x / GPE-y gel composite material for lithium batteries, wherein x=10 and y=30%.

[0068] Embodiment 14

[0069] The free radical scavenger in step 2) of Example 1 was changed to 30 mg, and the other conditions were the same as Example 1 to obtain a TA@β-x / GPE-y gel composite material for lithium batteries, wherein x=30 and y=30%.

[0070] Embodiment 15

[0071] The free radical scavenger in step 2) of Example 1 was changed to 40 mg, and the other conditions were the same as Example 1 to obtain a TA@β-x / GPE-y gel composite material for lithium batteries, wherein x=40 and y=30%.

[0072] Test results

[0073] According to the method and test conditions described in Example 1, the TA@β-x / GPE-y gel electrolyte assembled batteries prepared in Examples 2-15 were tested for discharge specific capacity at 5C, and the results are recorded in Table 1 together with the test results of Example 1.

[0074] Table 1 Performance test results of TA@β-x / GPE-y gel electrolyte prepared in Examples 1-15

[0075]

[0076] It can be seen from Table 1 that when the TA@β-x / GPE-y gel material prepared in the embodiment of the present invention is used in a lithium battery, under the harsh conditions of high voltage and high rate, the TA@β-x / GPE-y gel can inhibit the side reactions between the internal electrolyte and the electrode, thereby further improving the cycle stability of the battery.

[0077] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, various forms of changes can still be made to the technical solutions in the embodiments based on the above description. It is not necessary and impossible to give an exhaustive list of all implementation methods here. Any modification, change, replacement, etc. made on the basis of the technical content disclosed by the present invention are equivalent to equivalent implementation cases and should be included in the protection scope of the present invention.

Claims

1. A method for preparing a tannic acid TA@β nucleating agent doped gel electrolyte, characterized in that: The steps include: S1: Weigh tannic acid TA and β nucleating agent according to a mass ratio of 1:5 to 5:1, then mix them into water, stir at room temperature to react fully, separate, purify and dry to obtain TA@β free radical scavenger; S2: adding the free radical scavenger obtained in step S1, the phosphate monomer, and the acrylate monomer to the lithium salt electrolyte, and stirring and mixing; the free radical scavenger is 1 to 100 parts by weight, and the phosphate monomer and the acrylate monomer are both 200 to 600 parts by weight; Wherein, the lithium salt is one or a mixture of two or more selected from lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium tetrafluoroborate, lithium bis(difluorosulfonyl imide) and lithium bis(trifluoromethylsulfonyl imide); the phosphate monomer is one or a mixture of two or more selected from di[2-(methacryloyloxy)ethyl]phosphate, di[2-(acryloyloxy)ethyl]phosphate, vinyl dimethyl phosphate, vinyl diethyl phosphate, vinyl dipropyl phosphate, 2-(methacryloyloxy)ethyl-2-(trimethylamino)ethyl phosphate; the acrylate monomer is one or a mixture of two or more selected from trimethylolpropane triacrylate, cyanuric acid triacrylate, pentaerythritol tetraacrylate, 1,6-hexanediol diacrylate; S3: irradiating the mixed solution obtained in step S2 with γ rays or electron beams; after the irradiation, a new type of gel electrolyte is obtained.

2. The method for preparing the tannic acid TA@β nucleating agent doped gel electrolyte according to claim 1, characterized in that: In the step S1, the stirring reaction time at room temperature is 1-10 days.

3. The method for preparing the tannic acid TA@β nucleating agent doped gel electrolyte according to claim 1, characterized in that: In the step S1, the concentration of tannic acid is 5 to 50 g / L.

4. The method for preparing the tannic acid TA@β nucleating agent doped gel electrolyte according to claim 1, characterized in that: In the step S2, the mass concentration of the free radical scavenger is 0.1-10 g / L, and the mass concentrations of the phosphate monomer and the acrylate monomer are 20-60 g / L and 20-60 g / L respectively.

5. The method for preparing the tannic acid TA@β nucleating agent doped gel electrolyte according to claim 4, characterized in that: In step S2, the stirring time is 0.1-48h.

6. The method for preparing the tannic acid TA@β nucleating agent doped gel electrolyte according to claim 1, characterized in that: In the step S3, the irradiation absorbed dose rate is 10-150 Gy / min, and the absorbed dose is 0.1-20 kGy.

7. The method for preparing the tannic acid TA@β nucleating agent doped gel electrolyte according to claim 1, characterized in that: In step S3, the radiation source generating the gamma rays is 60 Co source or 137 Cs source; the electron beam is generated by an electron accelerator with an energy of 0.1 to 10 MeV.

8. A TA@β-doped gel electrolyte prepared by the method according to any one of claims 1 to 7.

9. Application of the TA@β doped gel electrolyte according to claim 8 in a lithium ion battery, characterized in that: At the position of the lithium-ion battery electrolyte, TA@β free radical scavenger, phosphate monomers, and acrylate monomers are added to the lithium salt electrolyte, stirred and mixed, and then injected, and the electrolyte is synthesized by in-situ polymerization through gamma rays or electron beams.

10. A lithium ion battery, characterized in that: The lithium-ion battery uses the TA@β-doped gel electrolyte described in claim 8 as an electrolyte.

Citation Information

Patent Citations

  • Preparation method and application of ionic gel electrolyte for lithium metal battery

    CN118146447A

  • In-situ polymerization gel electrolyte monomer, synthesis method thereof, polymerization gel electrolyte and gel battery

    CN118344353A

  • Monomer and polymer for gel electrolyte material, and preparation methods and applications of monomer and polymer

    CN106374139A

  • Composite gel electrolyte membrane, preparation method and application thereof

    CN113097578A

  • Gel polymer electrolyte and in-situ preparation method and application thereof

    CN117832600A